Use of a combination of phosphorous‐containing epoxy resin and silica fillers for development of flame retardant thermoset polymer composites. Issue 1 (14th October 2022) - Shree, Vibha; Sen, Akhil Kumar; Basu, Sayantani; Ratna, Debdatta
Abstract: In this paper, we report a method of preparation of ambient temperature curable phosphorous containing epoxy resin‐based composites and their flame retardant behavior. The phosphorous containing resin, prepared by reacting the epoxy resin with 9, 10‐Dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO), shows higher limiting oxygen index (LOI) in the cured state compared to the pure epoxy network. The LOI value is further enhanced due to the incorporation of phosphorous‐containing silica, although the same remains unchanged when pure silica is added. The composites made with phosphorous‐containing resin and pure silica exhibits UL‐94 V‐1 class rating whereas the same made with phosphorous‐containing silica offers V‐0 rating under UL‐94 classification. This observation clearly indicates that the performance is enhanced when phosphorous in incorporated in the resin as well as in the inorganic reinforcing filler. Abstract :